RANCANG BANGUN SISTEM INFORMASI PENGGAJIAN KARYAWAN (STUDI KASUS DI PT. RUMAH SAKIT PADJADJARAN JATINANGOR) - Kuwat Santoso (Universitas Maso'em Bandung, 2019)
PT. Padjadjaran Hospital Jatinangor Division of Padjadjaran Clinic requires the handling of a work system process that is fast and accurate to meet the demands of improving the quality of its human resources that have an impact on service to patients. Because still using a manual system results in frequent data and information inaccuracies.The design of SIstem Informasi Penggajian uses design tools in the form of System Development Life Cycle (SDLC). The diagrams used include: Data Flow Diagrams, Structure Charts, Flowmaps, and E-R Diagrams. This application uses Visual Studio 2010 with Vb.Net based on client server and Database uses MySQL with good security and data integration and supports transactional programs. After going through several stages of design, this application is expected to facilitate data collection and reporting and minimize data errors and provide a smooth payroll process.As for the advantages of this payroll application is to use the finger print machine so data validation will be guaranteed and employees will obey, discipline, and employees cannot manipulate attendance data.